2019
DOI: 10.1007/s00300-019-02533-0
|View full text |Cite|
|
Sign up to set email alerts
|

Benthic primary production and respiration of shallow rocky habitats: a case study from South Bay (Doumer Island, Western Antarctic Peninsula)

Abstract: Rocky benthic communities are common in Antarctic coastal habitats; yet little is known about their carbon turnover rates. Here, we performed a broad survey of shallow ( < 65 m depth) rocky ice-scoured habitats of South Bay (Doumer Island, Western Antarctic Peninsula), combining (i) biodiversity assessments from benthic imaging, and (ii) in situ benthic dissolved oxygen (O 2 ) exchange rates quantified by the aquatic eddy covariance technique. The 18 study sites revealed a gradual transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
(110 reference statements)
0
12
0
1
Order By: Relevance
“…Integrated primary production rates in open waters of the Arctic Ocean, estimated from remote sensing and closer to Net PP (or GPP-Respiration in Figure 2), are approximately 100 g C m −2 yr −1 (Arrigo and van Dijken, 2015; IOCCG, 2015), with production supported by winter nitrogen concentrations of 5-12 µM NO 3 (Codispoti et al, 2013). Known standing stocks of available nitrogen in the Arctic are not enough to support the annual Arctic Ocean production (Tremblay et al, 2015), meaning additional sources, either from advection or from diffusive processes, are required.…”
Section: Discussionmentioning
confidence: 97%
“…Integrated primary production rates in open waters of the Arctic Ocean, estimated from remote sensing and closer to Net PP (or GPP-Respiration in Figure 2), are approximately 100 g C m −2 yr −1 (Arrigo and van Dijken, 2015; IOCCG, 2015), with production supported by winter nitrogen concentrations of 5-12 µM NO 3 (Codispoti et al, 2013). Known standing stocks of available nitrogen in the Arctic are not enough to support the annual Arctic Ocean production (Tremblay et al, 2015), meaning additional sources, either from advection or from diffusive processes, are required.…”
Section: Discussionmentioning
confidence: 97%
“…In fjords, and at shelf depths, carbon standing stock and levels of sequestration are positively correlated with the functional diversity of the community, i.e., the number of different trophic groups, which is a measure of assemblage complexity [ 12 ]. The biodiversity of a few WAP rocky shores [ 22 , 23 ] and soft sediment shore assemblages in the shallows (e.g., at 20 m; [ 24 , 25 ]) have been described previously. However, the relationship between functional diversity, biomass and carbon standing stock is currently missing.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al (2007) y Day et al (2009) han evaluado la influencia del aumento de la temperatura y de las precipitaciones en el ecosistema analizando los flujos del carbono y el nitrógeno. La bahía Sur, situada en la isla Doumer del archipiélago de Palmer, ha sido base de estudios sobre flora y fauna bentónica (Cárdenas et al, 2016(Cárdenas et al, , 2018bRovelli et al, 2019), así como de oceanografía y meteorología (Cárdenas et al, 2018a;Villegas et al, 2018) constituyéndose en un diagnóstico de las condiciones actuales y sus variaciones locales. Siendo el archipiélago de Palmer una región de interés científico por la riqueza y variedad de sus ecosistemas, y teniendo en cuenta los importantes cambios en el clima en el sector oeste de la península Antártica (OPA) registrados a causa del calentamiento global (Kerr et al, 2018), así como las diferencias regionales y locales observadas al sur del archipiélago de Palmer, el presente artículo tiene como objetivo describir el comportamiento climatológico de algunos parámetros meteo-marinos de aguas circundantes al archipiélago y su tendencia durante el período 1979-2018.…”
Section: Introductionunclassified
“…Park et al (2007) and Day et al (2009) have evaluated the influence of the increase in temperature and precipitations in the ecosystem by analyzing carbon and nitrogen fluxes. The South Bay, located in the Doumer Island of the Palmer archipelago, has been the focus of studies on benthic flora and fauna (Cárdenas et al, 2016(Cárdenas et al, , 2018bRovelli et al, 2019), as well as on oceanography and meteorology (Cárdenas et al, 2018a;Villegas et al, 2018), thus constituting a diagnostic of current conditions and their local variations. Given that the Palmer archipelago is a region of scientific interest due to the richness and variety of its ecosystems, and considering the significant climate changes in the western sector of the Antarctic peninsula (WAP) caused by global warming (Kerr et al, 2018), as well as the regional and local differences observed in the South of Palmer archipelago, the objective of this article is to describe the climatological behavior of some meteo-marine parameters in the surrounding waters of the archipelago and their tendency during the period between descripción de variables tales como la Temperatura del aire (Ta), la Precipitación total (Pr), la Temperatura Superficial del Mar (TSM) y la Cobertura de Hielo Marino (CHM) en los últimos 40 años, permitirá tener un panorama de los posibles cambios ocurridos en estas características que servirán como base para futuros trabajos de variabilidad y cambio climático en sectores marinos que convergen en el archipiélago de Palmer.…”
Section: Introductionmentioning
confidence: 99%